History at Play in the Portrayal of Politicians in Canadian Drama - Green, Sean Douglas (Université d'Ottawa / University of Ottawa, 2016)
This thesis intends to focus on certain playwrights’ creative fascination and complex relationship with ‘politicians as subject’ who have been elevated to the rank of ‘greatness’ in part through their work. More specifically, it serves as a study into how playwrights mold certain politicians’ images, a type of creative investment that in turn helps craft, (re) affirm, or deconstruct the politician as a ‘cultural symbol.’ Using a historigraphic model based on Paul Ricoeur and Hayden White’s work, this thesis explores the dramaturgical approaches used by ‘artist-historian’ playwrights when creating dramatic figures inspired by Canadian politicians. In particular, it examines Linda Griffiths’ portrayal of Pierre Elliot Trudeau in Maggie and Pierre, David Fennario’s portrayal of René Lévesque in The Death of René Lévesque, and Allan Stratton’s portrayal of William Lyon Mackenzie King in Rexy!
Keywords: Drama; Canadian; Politician; Historiography